From Customer-Related Social Stressors to Emotional Exhaustion: An Application of the Demands–Control Model. (September 2019) - Ma, Zihui; Kim, Hyun Jeong; Shin, Kang Hyun
This study examines emotional intelligence (EI) as an additional moderator in the interactive effect of customer-related social stressors (CSS) (demands) and job autonomy (control) on emotional exhaustion by constructing a three-way interaction (EI × CSS × Autonomy) for the regression model of emotional exhaustion. Employees from hotels and restaurants in one metropolitan city in the United States participated in this study. The interactive effect of CSS and autonomy on exhaustion is shown among employees low in EI rather than high. Low EI employees experience greater exhaustion when they perceive low autonomy (stress exacerbating effect). When CSS is high, job autonomy is low, and EI is low, employees experience the highest level of emotional exhaustion. The findings support the proposition that individual characteristics, such as EI, add significant explanatory power to the job demands–control model (JDC) to understand occupational stress. Managerial and theoretical implications are provided based on the results.